Tough anti-fatigue hydrogel for buffering impact as well as preparation method and application of tough anti-fatigue hydrogel

Through linear polymer system and solvent space restriction strategy, high-energy absorption hydrogels were prepared, which solved the problem of insufficient energy absorption under high-frequency vibration and impact of existing hydrogels, and achieved high strength and fatigue resistance. Damping materials suitable for complex environments.

CN119219816AActive Publication Date: 2024-12-31ZHEJIANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411491949.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2024-12-31
Estimated Expiration
2044-07-23

AI Technical Summary

Technical Problem

Existing hydrogel damping materials cannot effectively absorb energy under high-frequency vibration and impact, and cannot take into account excellent strength and stability.

Method used

Using linear polymer system and solvent space restriction strategy, long-chain polyhydrogels without crosslinking points were prepared by irradiating precursors prepared by acrylamide, calcium chloride and initiator under vacuum, improving the Inter-chain interaction and energy absorption capacity.

Benefits of technology

It achieves high damping value, high modulus, high fracture strength, high toughness and high fatigue thresholds, and can absorb impact energy to a maximum extent under high-frequency impact, reduce peak amplification effect and displacement response, and adapt to complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219816A_ABST
    Figure CN119219816A_ABST
Patent Text Reader

Abstract

The invention discloses tough anti-fatigue hydrogel for buffering impact and a preparation method, and belongs to the field of novel soft materials. Based on the energy internal consumption design combining a long-chain linear polymer preparation strategy and a solvent space limitation strategy, the long-chain high-polymer hydrogel without cross-linking points is prepared by increasing the content of an acrylamide monomer in a precursor solution and utilizing the strong water binding capacity of hydrophilic salt calcium chloride. The prepared hydrogel is linear hydrogel with tough and anti-fatigue characteristics, chains in the linear hydrogel are more easily entangled, the linear hydrogel has higher interaction between the chains, the fracture toughness, the fatigue threshold and the energy absorption of the hydrogel can be effectively improved, and the hydrogel can be widely applied as a high-performance damping material.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent with application number 202410988197.8, application date July 23, 2024, and invention name "A strong and fatigue-resistant hydrogel for impact buffering and preparation method". Technical Field

[0002] The invention belongs to the field of novel soft materials, and in particular relates to a strong and tough anti-fatigue hydrogel for buffering impact and a preparation method thereof. Background Art

[0003] Damping materials, due to their efficiency in absorbing energy and reducing vibration, play a significant role in reducing noise, vibration and shock. Such materials play a key role in industries such as aerospace, automobile manufacturing, military and electronics. Application examples include anti-impact layers for micro-aircraft, sound insulation layers for automobile bodies, damping glue for microelectronic devices, protective soft armor, robot joint buffers, etc. These fields are in urgent need of high-performance damping materials. Although traditional damping materials, such as rubber, metal and their composite materials can meet basic needs, they are often difficult to meet higher performance requirements due to problems such as low loss factor, insufficient durability and heavy load.

[0004] As a unique soft material, hydrogels show great potential in the field of damping materials due to their excellent viscoelasticity and high water content. These materials can not only dissipate energy effectively, but also have good biocompatibility and the ability to adapt to changing environments. Nevertheless, the damping performance of most traditional hydrogels needs to be improved, and strengthening their toughness and fatigue resistance is also the main research direction at present.

[0005] At present, research on damping hydrogels is still preliminary. Inspired by spider foot pads, Park and other researchers developed a viscoelastic gelatin-chitosan hydrogel damper (Park B, Shin JH, Ok J, et al. Cuticular pad–inspired selective frequency damper for nearly dynamic noise–free bioelectronics [J]. Science, 2022, 376 (6593): 624-629.). The damper can dissociate the sticky bonds in the polymer matrix under the stimulation of external vibration, and rearrange the chitosan and gelatin chains to achieve frequency damping, effectively shielding noise below 30Hz. However, under high-frequency vibration and impact, its energy absorption effect is not good, and the displacement response during impact is large and the vibration duration is long. At the same time, the damper has a low modulus (less than 10kPa), which is not enough to adapt to complex environments.

[0006] On the other hand, Yuan et al. prepared chitin hydrogels by a binary solvent-induced self-assembly method. This method first promotes the formation of primary hierarchical fibers by pre-evaporation, and then performs binary solvent exchange to construct a two-dimensional layered microstructure to form a multilayered structure of nanocrystals (Yuan F, Zhang XX, Wu K, et al. Damping chitin hydrogels by harnessing insect-cuticle-inspired hierarchical structures [J]. Cell Reports Physical Science, 2023, 4 (11).). This structure achieves a certain degree of barrier and flexibility. However, it still cannot effectively buffer the impact. In the falling ball impact experiment, obvious rebound displacement can still be observed, indicating that its energy absorption effect needs to be further improved. Summary of the invention

[0007] The purpose of the present invention is to solve the defects of the prior art hydrogel damping materials that they cannot effectively absorb energy when facing high-frequency vibration and impact, and cannot take into account both excellent strength and stability, and to provide a strong and fatigue-resistant hydrogel for buffering impact and a preparation method.

[0008] The specific technical solutions adopted by the present invention are as follows:

[0009] In a first aspect, the present invention provides a method for preparing a strong and fatigue-resistant hydrogel for buffering impact, which comprises:

[0010] S1. Using water as solvent, add acrylamide, calcium chloride and initiator, and mix thoroughly to prepare a precursor solution, wherein the mass ratio of acrylamide to water is (1-2):1, and the mass ratio of calcium chloride to water is (0-2 / 3):1;

[0011] S2. placing the precursor solution in a transparent mold and irradiating it with ultraviolet light for 1 to 3 hours in a vacuum environment to obtain a strong and fatigue-resistant hydrogel.

[0012] As a preferred embodiment of the first aspect, when preparing the precursor solution, the mass ratio of calcium chloride to water is (0.25-2 / 3):1.

[0013] As a preferred embodiment of the first aspect, when preparing the precursor solution, the mass ratio of acrylamide to water is 1:1, and the mass ratio of calcium chloride to water is 2 / 3:1.

[0014] As a preferred embodiment of the first aspect, the ultraviolet wavelength used in the ultraviolet irradiation is 360-370nm, and the power is 35-45W.

[0015] Furthermore, the ultraviolet wavelength used in the ultraviolet irradiation is 365nm, the power is 40W, and the irradiation time is 3 hours.

[0016] As a preferred embodiment of the first aspect above, the initiator is photoinitiator 2959.

[0017] Furthermore, when preparing the precursor solution, the mass ratio of the initiator to the monomer is (0.0005-0.01):1.

[0018] Furthermore, when preparing the precursor solution, the mass ratio of the initiator to the monomer is 0.001:1.

[0019] In a second aspect, the present invention provides a strong and fatigue-resistant hydrogel for buffering impact, which is prepared by the preparation method described in any one of the schemes of the first aspect.

[0020] In a third aspect, the present invention provides a use of the tough and fatigue-resistant hydrogel for buffering impact as described in the second aspect as a damping material.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] In the design of the damping hydrogel, the present invention adopts a linear polymer system to avoid the storage of elastic potential energy of the cross-linked network in response to impact. The present invention can also introduce high spatial restrictions between polymer chains through the strong water binding ability of the hydrophilic salt calcium chloride, thereby improving the interaction between chains and further improving the damping effect.

[0023] The strong and tough anti-fatigue hydrogel prepared by the present invention has more excellent mechanical properties than existing damping materials, including high damping value, high modulus, high fracture strength, high toughness and high fatigue threshold. The strong and tough anti-fatigue hydrogel can absorb impact energy to a great extent under high-frequency impact, and at the same time has a very small peak amplification effect and displacement response, reducing the recovery time after impact. Due to the high energy absorption, only a small production volume is required to achieve impact barrier, and complex structures can be designed through 3D printing. In engineering applications, it can improve drag reduction efficiency, reduce consumables, reduce costs, and adapt to complex environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The figures are the tensile graphs and modulus and strength test result graphs of different hydrogels in the embodiments of the present invention;

[0025] Figure 2 Graph showing the tensile test results of different hydrogels in the embodiments of the present invention;

[0026] Figure 3 This is a graph showing the fracture toughness test results of different hydrogels in the embodiments of the present invention;

[0027] Figure 4 Graph showing dissipation test results of different hydrogels in embodiments of the present invention;

[0028] Figure 5 This is a fatigue threshold diagram of a highly spatially confined linear hydrogel in an embodiment of the present invention;

[0029] Figure 6 Graphs showing rheological sweep frequency and stress relaxation test results of different hydrogels in embodiments of the present invention;

[0030] Figure 7 Graph showing the results of a falling ball impact test on different hydrogels in an embodiment of the present invention. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation mode of the present invention is described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.

[0032] Existing hydrogel dampers can effectively block low-frequency noise, but cannot effectively absorb energy when facing high-frequency vibrations and impacts. At the same time, existing dampers cannot take into account both excellent strength and stability. Therefore, the present invention provides a strong and fatigue-resistant hydrogel for buffering impacts and a preparation method thereof. The preparation of high-damping hydrogel materials is achieved through an energy internal consumption design that combines a long-chain linear polymer preparation strategy with a solvent space restriction strategy. The material has a lower peak amplification effect and lower displacement and time response, and has both high toughness and fatigue resistance while having a high damping coefficient. The method for preparing the strong and fatigue-resistant hydrogel for buffering impacts is as follows:

[0033] S1. Use water as solvent, add acrylamide (AAm), calcium chloride (CaCl2) and initiator, mix thoroughly to prepare a precursor solution, wherein the mass ratio of acrylamide to water is (1-2):1, and the mass ratio of calcium chloride to water is (0-2 / 3):1.

[0034] S2. Place the above precursor solution in a transparent mold and irradiate it with ultraviolet light for 1 to 3 hours in a vacuum environment to obtain a strong and fatigue-resistant hydrogel.

[0035] Different from the conventional preparation of hydrogels with three-dimensional cross-linked networks, the preparation method of the present invention increases the content of acrylamide monomers in the precursor solution, that is, controls the mass ratio of AAm monomers to water within the range of 1:1 to 2:1, and simultaneously adds an initiator and irradiates with vacuum ultraviolet light to obtain a long-chain high-polymer hydrogel without cross-linking points. The hydrogel prepared by the present invention is a linear hydrogel with strong and anti-fatigue properties. The chains in the linear hydrogel are more easily entangled and have higher interchain interactions, which can effectively improve the fracture toughness, fatigue threshold and energy absorption of the hydrogel.

[0036] In the above-mentioned hydrogel preparation method, the ratio between the components and the selection of the initiator can be optimized according to actual conditions.

[0037] It should be noted that in the precursor solution, calcium chloride is not an essential component, and its content can be 0. Regulation of calcium chloride content can affect the linearity of the spatial restriction of the hydrogel finally obtained, and the higher the content of calcium chloride, the higher its spatial restriction, and as the spatial restriction is enhanced, the modulus and fracture strength of the hydrogel are improved. As the preferred embodiment of the present invention, when preparing the precursor solution, the mass ratio of calcium chloride to water is (0.25~2 / 3): 1, and when the mass ratio of calcium chloride to water reaches two-thirds to one (2 / 3: 1), the mass fraction of calcium chloride substantially reaches its solubility upper limit, that is, the mass fraction reaches 40%.

[0038] In addition, when preparing the above precursor solution, the content of acrylamide and calcium chloride also needs to be optimized. As a preferred embodiment of the present invention, the mass ratio of acrylamide to water is 1:1, and the mass ratio of calcium chloride to water is 2 / 3:1.

[0039] The type of initiator used in the present invention and its use can be optimized according to actual needs. The initiator type can be photoinitiator 2959, phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP for short), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO for short), α-ketoglutaric acid, dibenzoyl peroxide, etc. As a preferred embodiment of the present invention, the initiator uses photoinitiator 2959, and when used, ethanol can be used as a solvent to prepare a 2959-ethanol solution and add it to the precursor solution. When preparing the flooding liquid, the amount of the initiator can be determined by gradient optimization to determine the optimal amount. As a preferred embodiment of the present invention, the mass ratio of the initiator to the monomer is (0.0005-0.01):1, and more preferably 0.001:1.

[0040] It should also be noted that when the above-mentioned precursor liquid is placed in a transparent mold, it is necessary to keep the precursor liquid in a vacuum environment before ultraviolet irradiation to avoid contact with air. The simplest way to maintain a vacuum environment is to fill the inner cavity of the transparent mold with the precursor liquid. Of course, if the inner cavity is not filled, vacuumizing the excess air therein and then sealing to maintain the vacuum state can also meet the requirements.

[0041] The above-mentioned precursor solution can be placed in a UV curing box for UV irradiation for 1 to 3 hours to obtain a strong and anti-fatigue hydrogel. As a preferred embodiment of the present invention, the UV wavelength used for UV irradiation is 360 to 370 nm, the power is 35 to 45 W; further preferred, the UV wavelength is 365 nm, the power is 40 W, and the irradiation time is 3 hours.

[0042] The strong and anti-fatigue hydrogel prepared by the above preparation method of the present invention can be used as a damping material to manufacture various devices, such as a hydrogel damper. Moreover, since such a material has high energy absorption, only a small production volume is required to achieve impact barrier, and more complex structures can be designed through 3D printing to achieve various functions.

[0043] The specific preparation method of the above-mentioned strong and anti-fatigue hydrogel is demonstrated through several embodiments below to reflect its technical effect.

[0044] Example 1

[0045] Dissolve 5g of acrylamide AAM in 5ml of deionized water, add 0.25ml of 0.1mol / L 2959-ethanol solution, stir and shake thoroughly to form a precursor solution. In the precursor solution, the components are calculated according to the relative ratio, the mass ratio of AAM to water is 1:1, and the mass ratio of photoinitiator 2959 to AAM is 1:1000. Then pour the precursor solution into a closed acrylic mold, fill the mold cavity to form a vacuum environment, and then place the whole in a UV curing box with a UV wavelength of 365nm and a power of 40W. Irradiate with UV light for 3 hours to obtain a strong and fatigue-resistant hydrogel, which is recorded as PAAm-L spatially restricted linear hydrogel.

[0046] Example 2

[0047] Dissolve 5g acrylamide AAM and 0.56g CaCl2 in 5ml deionized water, add 0.25ml 0.1mol / L 2959-ethanol solution, stir and shake thoroughly to form a precursor solution. In the precursor solution, the mass ratio of AAM to water is 1:1, the mass ratio of calcium chloride to water is about 1:9 (10% by mass), and the mass ratio of photoinitiator 2959 to AAM is 1:1000. Then pour the precursor solution into a closed acrylic mold, fill the mold cavity to form a vacuum environment, and then place the whole in a UV curing box with a UV wavelength of 365nm and a power of 40W. Irradiate with UV light for 3 hours to obtain a strong and fatigue-resistant hydrogel, which is recorded as PAAm-10 spatially restricted linear hydrogel.

[0048] Example 3

[0049] Dissolve 5g acrylamide AAM and 1.25g CaCl2 in 5ml deionized water, add 0.25ml 0.1mol / L 2959-ethanol solution, stir and shake thoroughly to form a precursor solution. In the precursor solution, the mass ratio of AAM to water is 1:1, the mass ratio of calcium chloride to water is about 0.25:1 (20% by mass), and the mass ratio of photoinitiator 2959 to AAM is 1:1000. Then pour the precursor solution into a closed acrylic mold, fill the mold cavity to form a vacuum environment, and then place the whole in a UV curing box with a UV wavelength of 365nm and a power of 40W. Irradiate with UV light for 3 hours to obtain a strong and fatigue-resistant hydrogel, which is recorded as PAAm-20 spatially restricted linear hydrogel.

[0050] Example 4

[0051] Dissolve 5g acrylamide AAM and 3.33g CaCl2 in 5ml deionized water, add 0.25ml 0.1mol / L 2959-ethanol solution, stir and shake thoroughly to form a precursor solution. In the precursor solution, the mass ratio of AAM to water is 1:1, the mass ratio of calcium chloride to water is about 2:3 (40% by mass), and the mass ratio of photoinitiator 2959 to AAM is 1:1000. Then pour the precursor solution into a closed acrylic mold, fill the mold cavity to form a vacuum environment, and then place the whole in a UV curing box with a UV wavelength of 365nm and a power of 40W. Irradiate with UV light for 3 hours to obtain a strong and fatigue-resistant hydrogel, which is recorded as PAAm-H spatially restricted linear hydrogel.

[0052] Example 5

[0053] Dissolve 2.5g acrylamide AAM and 6.66g CaCl2 in 10ml deionized water, add 0.125ml 0.1mol / L 2959-ethanol solution, stir and shake thoroughly to form a precursor solution. In the precursor solution, the mass ratio of AAM to water is 0.25:1, the mass ratio of calcium chloride to water is about 2:3 (40% by mass), and the mass ratio of photoinitiator 2959 to AAM is 1:1000. Then pour the precursor solution into a closed acrylic mold, fill the mold cavity to form a vacuum environment, and then place the whole in a UV curing box with a UV wavelength of 365nm and a power of 40W. Irradiate with UV light for 3 hours to obtain a strong and fatigue-resistant hydrogel, which is recorded as 0.25:1PAAm-H spatially restricted linear hydrogel.

[0054] Example 6

[0055] Dissolve 5g acrylamide AAM and 6.66g CaCl2 in 10ml deionized water, add 0.25ml 0.1mol / L 2959-ethanol solution, stir and shake thoroughly to form a precursor solution. In the precursor solution, the mass ratio of AAM to water is 0.25:1, the mass ratio of calcium chloride to water is about 2:3 (40% by mass), and the mass ratio of photoinitiator 2959 to AAM is 1:1000. Then pour the precursor solution into a closed acrylic mold, fill the mold cavity to form a vacuum environment, and then place the whole in a UV curing box with a UV wavelength of 365nm and a power of 40W. Irradiate with UV light for 3 hours to obtain a strong and fatigue-resistant hydrogel, which is recorded as 0.5:1PAAm-H spatially restricted linear hydrogel.

[0056] Example 7

[0057] Dissolve 20g acrylamide AAM and 6.66g CaCl2 in 10ml deionized water, add 1ml 0.1mol / L 2959-ethanol solution, stir and shake thoroughly to form a precursor solution. In the precursor solution, the mass ratio of AAM to water is 0.25:1, the mass ratio of calcium chloride to water is about 2:3 (40% by mass), and the mass ratio of photoinitiator 2959 to AAM is 1:1000. Then pour the precursor solution into a closed acrylic mold, fill the mold cavity to form a vacuum environment, and then place the whole in a UV curing box with a UV wavelength of 365nm and a power of 40W. Irradiate with UV light for 3 hours to obtain a strong and fatigue-resistant hydrogel, which is recorded as 2:1PAAm-H spatially restricted linear hydrogel.

[0058] In the above-mentioned Examples 1, 2, 3 and 4, the mass percentage of calcium chloride (i.e., the mass of calcium chloride divided by the total mass of calcium chloride and water) is 0, 10%, 20% and 40%, respectively, and PAAm-L, PAAm-10, PAAm-20 and PAAm-H spatially restricted linear hydrogels are obtained, respectively, wherein PAAm-L and PAAm-H correspond to low spatially restricted linear hydrogels and high spatially restricted linear hydrogels, respectively, and PAAm-10 and PAAm-20 are spatially restricted linear hydrogels between the two. In the above-mentioned Examples 5, 6 and 7, the mass percentage of calcium chloride is 40%, which belongs to high spatially restricted linear hydrogels, but compared with the PAAm-H obtained in Example 4, the difference is that the monomer concentration, i.e., the ratio of AAM monomer to water is different. The ratio of AAM monomer to water in Example 4 is 1:1, but the ratios of AAM monomer to water in Examples 5, 6 and 7 are 0.25:1, 0.5:1 and 2:1, respectively. Therefore, the highly spatially confined linear hydrogels obtained in Examples 5, 6 and 7 are recorded as 0.25:1 PAAm-H, 0.5:1 PAAm-H and 2:1 PAAm-H.

[0059] In order to demonstrate the effect of different ratio parameters on the performance of the final hydrogel, mechanical strength characterization tests were carried out on the above-mentioned PAAm-L, PAAm-10, PAAm-20, PAAm-H, 0.25:1PAAm-H, 0.5:1PAAm-H, and 2:1PAAm-H hydrogels, and different characterization results are shown below.

[0060] 1. The four spatially confined linear hydrogels PAAm-L, PAAm-10, PAAm-20 and PAAm-H were subjected to uniaxial tensile tests. In this embodiment, the loading rate was 100 mm / min (the tensile test below is all at this tensile rate unless otherwise specified), the sample used was 50 mm long × 10 mm wide × 2 mm thick, the modulus was calculated based on the first 10% of the tensile curve, and the maximum strength was obtained based on the maximum stress. The results are shown in the figure. Figure 1 As shown. Figure 1 It can be seen that with the increase of CaCl2 content, the spatial confinement of the hydrogel is enhanced, and the modulus and breaking strength of the hydrogel are improved.

[0061] 2. The same uniaxial tensile test was performed on three highly spatially confined linear hydrogels of 0.25:1PAAm-H, 0.5:1PAAm-H, and 2:1PAAm-H with different monomer concentrations. Figure 2 The tensile diagrams of three highly spatially confined linear hydrogels with different monomer concentrations are shown, from which it can be seen that as the monomer concentration decreases, the modulus and breaking strength of the PAAm-H hydrogel decrease significantly. Therefore, the optimal ratio of AAM monomer to water is 1:1 to 2:1.

[0062] 3. The fracture toughness of four spatially confined linear hydrogels, PAAm-L, PAAm-10, PAAm-20, and PAAm-H, was tested. In this embodiment, a pure shear test of 10 mm long × 50 mm wide × 2 mm thick was used to perform tensile tests on cracked and non-cracked samples to obtain fracture toughness. Fracture toughness is an important indicator to characterize the material's resistance to crack propagation. Figure 3 The fracture toughness test results of four spatially confined linear hydrogels, PAAm-L, PAAm-10, PAAm-20, and PAAm-H, are shown. It can be seen that the fracture toughness of PAAm-H highly spatially confined linear hydrogel reaches 3800 J / m 2 The fracture toughness of the low spatial confinement linear hydrogel of PAAm-L is increased by 6 times.

[0063] 4. Dissipation test was performed on PAAm-L, PAAm-10, PAAm-20 and PAAm-H spatially confined linear hydrogels. In this embodiment, the dissipation test was performed using a sample of 50 mm long × 10 mm wide × 2 mm thick, and loading and unloading were performed under elongation conditions of 2, 3 and 4, respectively. The dissipation ratio was obtained by comparing the area enclosed by the loading and unloading curves with the area under the loading curve. Figure 4 The dissipation test results of four linear hydrogels with different spatial confinement show that the linear hydrogel PAAm-H with high spatial confinement has good elasticity under low-frequency (about 0.16 Hz) load and is not prone to residual deformation.

[0064] 5. Fatigue test on highly spatially confined linear hydrogel PAAm-H. Figure 5 The fatigue threshold diagram of PAAm-H is shown, with the vertical axis representing the crack growth rate and the horizontal axis representing the corresponding energy release rate. The intercept of the X-axis represents the fatigue threshold of the hydrogel, that is, under a cyclic load lower than the energy release rate, the cracked hydrogel will not expand. The results show that the highly spatially confined linear hydrogel PAAm-H has excellent fatigue resistance.

[0065] 6. The viscoelasticity of the low spatial confinement linear hydrogel PAAm-L and the high spatial confinement linear hydrogel PAAm-H was characterized. In this embodiment, the viscoelasticity was characterized by a rheometer at room temperature of 20°C, using a shear strain of 0.5%, and sweeping the frequency from 0.1 to 100 to obtain the tangent value of the loss angle - the loss coefficient; at the same time, a stress relaxation experiment was performed, using a 50mm long × 10mm wide × 2mm thick strip sample, stretched to 2 times the elongation at 100mm / min and maintained, to obtain the stress relaxation result. Figure 6The results of rheological sweep frequency and stress relaxation experiments of the two hydrogels show that the high spatial confinement linear hydrogel PAAm-H has a higher loss coefficient at high frequencies than the low spatial confinement linear hydrogel PAAm-L, and there is still a trend of continued increase, indicating that the high spatial confinement linear hydrogel PAAm-H can effectively block high-frequency loads.

[0066] 7. Impact resistance test was performed on PAAm-L, PAAm-10, PAAm-20 and PAAm-H spatially confined linear hydrogels. In the impact resistance test of this embodiment, an iron ball with a diameter of 25 mm was dropped from the same height (20 cm), and the energy absorption ratio before and after the impact was calculated based on the height of the iron ball rebounding after impacting the hydrogel. Figure 7 The results of the drop ball impact test of the spatially restricted linear hydrogel are shown, from which it can be seen that as the spatial restriction increases, the energy absorption ratio of the hydrogel increases from 67% to 98%. It can be seen that the PAAm-H high spatial restriction linear hydrogel designed by the present invention can effectively block the impact and is an excellent damping hydrogel, but even the PAAm-L low spatial restriction linear hydrogel has good damping performance, and its energy absorption ratio has reached 67%, which can fully meet the application requirements in some scenarios with low requirements for damping performance.

[0067] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for preparing a strong and fatigue-resistant hydrogel for buffering impact, characterized in that: include: S1. Using water as solvent, add acrylamide, calcium chloride and initiator, and mix thoroughly to prepare a precursor solution, wherein the mass ratio of acrylamide to water is (1-2):1, and the mass ratio of calcium chloride to water is (0-2 / 3):1; S2. placing the precursor solution in a transparent mold and irradiating it with ultraviolet light for 1 to 3 hours in a vacuum environment to obtain a strong and fatigue-resistant hydrogel.

2. The method for preparing a strong and anti-fatigue hydrogel for shock buffering according to claim 1, characterized in that: When preparing the precursor solution, the mass ratio of calcium chloride to water is (0.25-2 / 3):

1.

3. The method for preparing a strong and fatigue-resistant hydrogel for buffering impact according to claim 1, characterized in that: When preparing the precursor solution, the mass ratio of acrylamide to water is 1:1, and the mass ratio of calcium chloride to water is 2 / 3:

1.

4. The method for preparing a strong and anti-fatigue hydrogel for shock buffering according to claim 1, characterized in that: The ultraviolet wavelength used in the ultraviolet irradiation is 360-370nm, and the power is 35-45W.

5. The method for preparing a strong and anti-fatigue hydrogel for shock buffering according to claim 4, characterized in that: The ultraviolet wavelength used in the ultraviolet irradiation is 365nm, the power is 40W, and the irradiation time is 3 hours.

6. The method for preparing a strong and fatigue-resistant hydrogel for shock buffering according to claim 1, characterized in that: The initiator is photoinitiator 2959.

7. The method for preparing a strong and fatigue-resistant hydrogel for shock buffering according to claim 6, characterized in that: When preparing the precursor solution, the mass ratio of the initiator to the monomer is (0.0005-0.01):

1.

8. The method for preparing a strong and fatigue-resistant hydrogel for shock buffering according to claim 7, characterized in that: When preparing the precursor solution, the mass ratio of the initiator to the monomer is 0.001:

1.

9. A strong and fatigue-resistant hydrogel for impact buffering prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the strong and fatigue-resistant hydrogel for buffering impact as claimed in claim 9 as a damping material.

Citation Information

Patent Citations

  • Preparation method of full-physical cross-linked triple interpenetrating network hydrogel

    CN110591121A

  • Anti-icing hydrogel bonding material as well as preparation method and application thereof

    CN111234122A

  • Anti-fatigue all-hydrogel composite material as well as preparation method and application thereof

    CN112111073A

  • Method for preparing high-strength, high-tensile and anti-fatigue hydrogel without cross-linking reaction

    CN116715874A

  • Simple preparation method of tough water-soluble self-repairing high polymer material based on reducing sugar initiated polymerization

    CN117843843A